A Review of Edible Jujube, the Ziziphus jujuba Fruit: A Heath Food Supplement for Anemia Prevalence - Chen, Jianping; Tsim, Karl W. K. (Frontiers in Pharmacology, 2020)
The fruits of Ziziphus jujuba, commonly known as jujube, red date or Chinese date, are taken as fresh or dried food, and as traditional medicine worldwide due to high nutritional and health values. Traditionally in China, jujube is considered as a medicinal fruit that is being used in treating blood deficiency. In this review, the beneficial effects of jujubes on the hematopoietic functions are summarized and discussed. As illustrated in cell and animal models, the application of jujube extract possessed beneficial effects, including regulation of erythropoiesis via activation of hypoxia inducible factor-induced erythropoietin, potential capacity in recycling heme iron during erythrophagocytosis and bi-directional regulation of immune response. Thus, the blood-nourishing function of jujube is being proposed here. Flavonoid, polysaccharide and triterpenoid within jujube could serve as the potential active ingredients accounting for the aforementioned health benefits. Taken together, these findings provide several lines of evidence for further development of jujube as supplementary products for prevention and/or treatment of anemia.